The Supply Chain Role of Transaction Processing System in Customer Relationship Management - Samira Ahmed Mahdi Al-Jnabi; Salah Aldeen Awad Kareem (International Journal of Supply Chain Management, 2018)
The aim of this study is to examine the supply chain role of the Transaction Processing System (TPS) on customer relationship management using empirical analysis. The study employed the opinions of 47 managers from selected banks in Baghdad that are known for the use of TPS through the collection and transaction store or from the decision-makers in the organizations. The result showed that there is a correlation between TPS and effective use of customer relationship management except when data are interned.